Spectrophotometric Determination of the CuSO4 Soret Coefficient of a CuSO4-H2O Binary Solutions System - Ijang Rohman; Djaka Sasmita; Iip Izul Falah (Universitas Gadjah Mada, 2001)
A spectrophotometric technique for the determination of the CuSO4 soret coefficient of a CuSO4-water binary solutions system is described. A short column of solutions is placed between horizontal metal plates that are held at different temperatures. The subsequent changes in composition due to thermal diffusion are followed by monitoring changes of transmittance near the end of the solutions column. In water, CuSO4 diffuses to the warm compartment of column. The soret coefficient of CuSO4 0.0254 molal in water agrees with the appropriate theory, i.e. 17.60x10-3 °C-1 on the average.